Beta-blockers and COPD: the show must go on. Issue 3 (September 2016) - Lopez-Campos, Jose Luis; Márquez-Martín, Eduardo; Casanova, Ciro
Identification of comorbidities is now recognised as one of the pillars for a comprehensive clinical evaluation in chronic obstructive pulmonary disease (COPD) [1]. Specifically, the burden of coexisting cardiovascular disease in COPD has gained significant attention, with specific algorithms being developed for its clinical detection [2]. The relationship between the heart and COPD is of clinical relevance not only for the well-documented relationship between the two organs [3], but also for the potential mutual influence of treatments. The interactions between oral beta-blockers and inhaled β-adrenergic drugs pose significant challenges for clinicians involved in the management of patients with chronic cardiorespiratory conditions. In particular, the use of beta-blockers in COPD remains the subject of ongoing controversy [4]. Current evidence on beta-blockers efficacy and safety in COPD is encouraging but limited with future studies needed http://ow.ly/IaNL301YANI